Depression-/Anxiety-Like Behavior Alterations in Adult Slit2 Transgenic Mice - Huang, Guilan; Wang, Sheng; Yan, Jie; Li, Changxi; Feng, Jianwen; Chen, Qi; Zheng, Xiaomeng; Li, Huimin; He, Yajun; Young, Andrew J.; Li, Haobin; Li, Weidong; et al. (Frontiers in Behavioral Neuroscience, 2021)
Background: Slit2 is a member of the Slit family of secreted glycoproteins that plays highly conserved roles in neuronal axon guidance and cellular migration. Our previous experimental results showed Alzheimer’s disease-like alterations and increased permeability of the blood-brain barrier in Slit2 overexpressing transgenic (Slit2-Tg) mice aged 8~9 months. Nevertheless, relatively little is known about behavioral alterations in adult Slit2-Tg mice (2~6 months of age). To observe the age-related behavioral effects of Slit2 overexpression in adult mice, we performed a battery of behavioral tests with adult Slit2-Tg mice at 2~6 months of age. Results: The body weight of Slit2-Tg mice was lower than wildtype mice from 15 weeks of age. Compared with the control mice, depression-like behaviors were found in Slit2-Tg mice from 15 weeks to 21 weeks of age in the sucrose preference test, although Slit2-Tg mice were hyperactive in the tail suspension test. The anxiety-like behaviors were found in Slit2-Tg mice in the open field test, as well as increased locomotor activity. The anxiety-like behaviors were also found in adult Slit2-Tg mice in the elevated plus maze. Compared to wildtype mice at 23-week-old, impairment of the hippocampal neurons were found in Slit2-Tg mice at the same age in Haematoxylin-eosin staining (H&E), including some eccentric dispersion and expansion of neuronal bodies. In addition, the mRNA expression of TNF-α was elevated in the hippocampus of adult Slit2-Tg mice. Conclusions: Slit2 overexpression cause depression/anxiety-like behaviors in adult mice that may be related to an increase in inflammatory factors and damage to hippocampal neurons.